Evaluating the Perception of Others in a Remote Experience of Interaction: a Pilot Study - Mendoza, Yusseli Lizeth Méndez; Duarte, Emanuel Felipe; Baranauskas, M. Cecília C. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2022)
The social and physical distancing and the rapid transition to remote learning during pandemics had an impact on children's well-being. In this context, the Human-Computer Interaction (HCI) field envisaged challenges to design and evaluate computational systems. In this paper, we propose an evaluation instrument considering socio-affective aspects of the experience, and present results from a pilot study to evaluate the Aquarela Virtual system. The Aquarela Virtual system allows remotely situated children to interact in a playful way with others by using physical objects related to a children's song, and emoticons to express their emotions. Based on findings of these evaluations, we provide insights on other aspects to be covered by our proposed evaluation instrument, and improvements in the system.